Regio‐, and Stereoselective Iodobromination of Ynamides for Synthesis of (E)‐1‐Bromo‐2‐iodoenamides. Issue 15 (9th April 2014) - Ide, Masataka; Yauchi, Yuta; Iwasawa, Tetsuo
Abstract: One‐step synthesis of vicinal bromoiodoenamides from ynamides through IBr addition is described. Two types of IBr were used: commercially available IBr, and in situ generated IBr. This simple protocol enables highly efficient regio‐ and stereoselective iodobromination of the triple bond on a gram scale in anti ‐mode, and provides a potentially diverse scaffold for preparation of tetrasubstituted olefins. Abstract : Highly regio‐, and stereoselective addition reactions of IBr to ynamide were achieved by using either commercially available and/or in situ generated IBr. The method results in a single ( E )‐isomer product, and provides general entry to potentially diverse 1‐bromo‐2‐iodoenamide scaffolds bearing carbamate, indole, and benzyl tosylamide.